2014
DOI: 10.1080/13811118.2013.801816
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Prisoners Who Make or Do Not Make Suicide Attempts and Further Who Make One or Multiple Attempts

Abstract: Suicidal behavior among prisoners is a major problem. The objective of this study was to compare prisoners who have made an attempt at suicide vs non-attempters and further to compare single vs multiple suicide attempts. Among 1,537 prisoners, 200 (13%) had a lifetime history of attempting suicide and 92 (6%) had made multiple attempts. Those who had made multiple or single attempts were compared on socio-demographic, developmental, personality, forensic, and psychiatric variables. In a re-analysis we also com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
2
7
2
Order By: Relevance
“…So, our sample might have higher levels of psychopathology than prison populations. Despite these differences, however, rates of Thomson et al self-harm among the fire setters in our cohort were similar to those reported in earlier studies of prisoners (Bland et al, 1990;Jenkins et al, 2005;Roy et al, 2014), suggesting that risk of attempted suicide is elevated by factors associated with being an offender rather than fire setting per se. To verify this, a follow-up study to compare suicide attempts between arsonists and prisoners of other types of crimes is needed in the future.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…So, our sample might have higher levels of psychopathology than prison populations. Despite these differences, however, rates of Thomson et al self-harm among the fire setters in our cohort were similar to those reported in earlier studies of prisoners (Bland et al, 1990;Jenkins et al, 2005;Roy et al, 2014), suggesting that risk of attempted suicide is elevated by factors associated with being an offender rather than fire setting per se. To verify this, a follow-up study to compare suicide attempts between arsonists and prisoners of other types of crimes is needed in the future.…”
Section: Discussionsupporting
confidence: 84%
“…Approximately 14-23% of male prisoners have attempted suicide in their lifetime (Bland et al, 1990;Jenkins et al, 2005;Sarchiapone et al, 2009). According to a study by Roy et al (2014), 13% of a prison sample of 1537 men had a lifetime history of attempted suicide; 6% had made multiple attempts. Prisoners with multiple attempts were more introverted and less resilient and more likely to have a history of self-mutilation than those with only one suicide attempt.…”
Section: Introductionmentioning
confidence: 99%
“…These findings echo earlier data relating to 1990-2002 (Preti & Cascio, 2006). Unfortunately, despite such high rates of suicide in Italian prisons, few individualbased studies have been carried out in Italy in order to investigate suicide risk factors in inmates (Carli et al, 2011;Roy et al, 2014;Sarchiapone, Carli, Di Giannantonio, & Roy, 2009;Sarchiapone, Jovanovic, et al, 2009;Verdolini et al, 2017). Nonetheless, efforts to enhance prevention strategies in prisons were recently carried by the Italian government through the approval of a national action plan on suicide prevention in prisons (Conferenza Unificata Stato-Regioni).…”
Section: Introductionsupporting
confidence: 86%
“…Suicide attempts have also been observed to be more frequent in inmates than non-inmates (Jenkins et al, 2005;Sarchiapone, Jovanovic, et al, 2009;Wichmann, Serin, & Motiuk, 2000). Previous suicide attempts and self-injury are amongst the main risk factors for suicide in inmates (Carli et al, 2011;Fazel, Cartwright, Norman-Nott, & Hawton, 2008;Fruehwald, Matschnig, Koenig, Bauer, & Frottier, 2004;Hawton, Linsell, Adeniji, Sariaslan, & Fazel, 2014;Humber, Webb, Piper, Appleby, & Shaw, 2013;Roy, Carli, Sarchiapone, & Branchey, 2014;Verdolini et al, 2017). Other risk factors appear to be specifically related to the prison environment (Dye, 2010;Fazel et al, 2008;World Health Organization, 2007), Indeed, suicidal behaviours in prisons are likely due to complex interactions between individual-level (such as the types of crimes committed before incarceration (Fazel et al, 2008;Hawton et al, 2014;Rabe, 2012;Verdolini et al, 2017), and ecological factors (Jenkins et al, 2005), including the nature and quality of prison environments and regimes (Dye, 2010;Fazel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among prisoners, anger and hostility scores differentiate also those who had attempted suicide (Roy et al 2014 ). Furthermore, hostility was found to be higher in depressed attempters with siblings concordant for SBs (Brent et al 2003 ).…”
Section: Hostility Anger and Other Personality Traitsmentioning
confidence: 97%